Strategi penguatan kapasitas aparatur pengelola dana desa melalui pelatihan revolusi mental - Sulsalman Moita (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Community Partnership Program (PKM) partners are Lalonggowuna Village and Momea Village. The problems are: (1) The Mental Revolution Movement has yet to understand in raising awareness, being honest and optimistic in the apparatus of village fund managers in utilizing it for the independence and welfare of the community; (2) Insufficient capacity of the apparatus in village fund management so that its utilization is expected to be carried out in a transparent, accountable, and participatory manner. The targets achieved in this PKM are: 1) The resulting strategy of strengthening the capacity of the apparatus through the mental revolution movement to be a reference in the utilization of KKN-free village funds; 2) The creation of scientific journals that can be a reference both for the development of science and for practitioners to produce a model of using funds based on the values of the mental revolution movement. The method used is training by focusing on the FGD approach, which emphasizes identifying potential and opportunities for misuse of village funds that have the potential to violate the law; deepening the strategic values of the mental revolution movement by the apparatus, concretisation and patterns of the mental revolution movement through strengthening kaspitas, knowledge, integrity, commitment, and responsibility through the exchange of information and experience. PKM results show that: 1) Partners have the ability to adopt material 3 mental revolutionary movements in the management and utilization of village funds through the serving movement, orderly movement, and clean movement; 2) partners have the skills to utilize training material through the practice of mental revolution movements through simulation forums and FGDs; 3) partners are committed to utilizing training materials for managing village funds that are transparent, accountable, and participatory.